Charge and Heat Transport Phenomena in Electronic and Spin Structures in B20-type Compounds - Kanazawa, Naoya; SpringerLink (Online service) (Tokyo : Springer Japan : Imprint: Springer, 2015)
This thesis presents systematic experimental research on chiral-lattice crystals referred to as B20-type germanium compounds, especially focusing on skyrmion spin textures and Dirac electrons. An emergent electromagnetic field observed in MnGe demonstrates a formation of three-dimensional skyrmion crystals. Detection of skyrmions in nanoscale Hall bar devices made of FeGe is realized by measuring the topological Hall effect, a transport property reflecting emergent fields produced by skyrmions. By measuring the electron-filling dependence of thermopower in CoGe, a pronounced thermoelectric property in this compound is revealed to stem from the asymmetric density of states appearing at certain levels of Fermi energy in the Dirac electron state. The three main results named above will contribute to enriching a variety of novel electromagnetic responses of emergent gauge fields in solids, to realizing high-performance skyrmion-based magnetic memory, and to designing high-efficiency thermoelectric materials, respectively.
Introduction -- Experimental methods -- Magnetic and transport properties in B20-type germanides -- 3D skyrmion-lattice and topological Hall effect in MnGe -- Skyrmion formation in epitaxial FeGe thin films -- 3D Dirac electrons and large thermoelectric properties in CoGe -- Conclusion.
Keywords: Superconductivity; Superconductors; Surfaces (Physics).; Interfaces (Physical sciences).; Thin films; Phase transformations (Statistical physics).; Condensed materials; Materials—Surfaces.; Strongly Correlated Systems, Superconductivity; Surface and Interface Science, Thin Films; Quantum Gases and Condensates; Surfaces and Interfaces, Thin Films